Effectiveness of Infant Massage Using Aromatherapy Essentialoil of Ylang-ylang Flower on Sleep Quality Sleep Quality of Infants 6-12 Months at Posyandu Arjuna Neighborhood IV Sei Renggas Village - Mahyunidar; Sitorus, Ririn Anggriani; Yunita, Sukma (International Journal of Public Health Excellence (IJPHE), 2023)
In Indonesia, 44.2% of children experience difficulties with sleep onset, yet 72% of parents perceive this to be a minor issue. Conversely, sleep disorders have been linked to adverse effects on infant growth, immune system function, and the regulation of the endocrine system. To enhance the quality of sleep and facilitate optimal child growth and development, infant massage may be a viable solution. The objective of this research is to investigate the potential benefits of infant massage using aromatherapy essential oils, specifically ylang-ylang flower, on the sleep quality of infants aged 6-12 months. The objective of this study is to determine the effectiveness of infant massage using aromatherapy essential oil of ylang-ylang flower on the quality of sleep of infants aged 6-12 months at Posyandu Arjuna Lingkungan IV Sei Renggas Village. Methodology In this study, the researchers employed a quantitative research methodology. The results of the study are as follows: The results of the Wilcoxon test indicate a p-value of 0.000 (p < 0.05), which rejects the null hypothesis (Ho). This suggests that there is a statistically significant difference in the quality of sleep of infants aged 6-12 months before and after receiving a massage using aromatherapy essential oil ylang ylang flowers. In conclusion, the results of this study indicate that infant massage using aromatherapy essential oil of ylang-ylang flower is an effective method for improving the quality of sleep in infants aged 6-12 months. A significant difference was observed in the quality of sleep of infants aged 6-12 months before and after baby massage using ylang ylang essential oil aromatherapy, with a p-value of 0.000 (p < 0.05). The use of baby massage with ylang ylang essential oil aromatherapy effectively improves sleep quality in infants aged 6-12 months at Posyandu Arjuna.